Competição entre bolsas de futuros: o caso da BM&F e da CSCE no mercado de café - Lazzarini, Sérgio G.; Saes, Maria Sylvia M.; Nakazone, Douglas (Economia Aplicada, 2000)
This study discusses the competition between futures exchanges as evaluated by their users, in particular hedgers, choosing alternative contracts based on costs and benefits of hedging. Focusing on Brazilian hedgers, two alternative exchanges supplying coffee futures contracts are evaluated: the Coffee, Sugar and Cocoa Exchange (CSCE), and the Brazilian Commodities and Futures Exchange (BM&F), the latter with contracts more specifically designed to the physical, temporal and locational characteristics of the Brazilian coffee. Results suggest that liquidity is the most important factor influencing the negotiation of contracts on the CSCE market by Brazilian traders, even though there is evidence that hedging effectiveness tends to be higher for the BM&Fcontract. An analysis ofthe future price bias ("risk premium") embodied in the contracts did not allow us to reject the hypothesis that there is no significant difference between the exchanges with regard to this aspect. Institutional and dynamic issues are also briefly discussed.